2020
DOI: 10.1111/and.13834
|View full text |Cite
|
Sign up to set email alerts
|

The protective effect of melatonin on radiofrequency electromagnetic fields of mobile phone‐induced testicular damage in an experimental mouse model

Abstract: Radiofrequency electromagnetic radiation (RF‐EMR) from mobile devices has undesirable effects on the male reproductive organs. Melatonin with antioxidant potential can help to prevent these damages. Therefore, the aim of this study was to evaluate the protective effect of melatonin on testicular damage induced by RF‐EMR of mobile phone. In this experimental study, 32 adult male BALB/c mice were divided randomly into four groups: control, melatonin (2 mg/kg, for 30 consecutive days, intraperitoneally), RF‐EMR (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 45 publications
0
7
1
Order By: Relevance
“…In fact, reproductive organs, especially in the male, are very sensitive to environmental stresses such as EMFs due to radiofrequency electromagnetic radiation [76]. Moreover, these results are linked to the increase observed also in melatonin in the present study since the antioxidant effect of melatonin seems to help to prevent that damage in reproductive organs [77], although the results were not obtained in the same people.…”
Section: Discussioncontrasting
confidence: 46%
“…In fact, reproductive organs, especially in the male, are very sensitive to environmental stresses such as EMFs due to radiofrequency electromagnetic radiation [76]. Moreover, these results are linked to the increase observed also in melatonin in the present study since the antioxidant effect of melatonin seems to help to prevent that damage in reproductive organs [77], although the results were not obtained in the same people.…”
Section: Discussioncontrasting
confidence: 46%
“…But melatonin normalised the level of vitamin E and prevented EMR‐induced oxidative damage in the testicles by strengthening the antioxidant redox system (Oksay et al, 2014). In a study by Shokri et al, it was reported mobile phone EMR (900 MHz) reduced testosterone levels and caused testicular tissue damage in mice models, but melatonin treatment reduced oxidative stress parameters such as MDA and GSH levels and diameter of the seminiferous tubules, and increased the thickness of the germinal epithelium and testosterone levels of EMR‐exposed mice (Shokri et al, 2020).…”
Section: Melatonin and Signalling Pathwaysmentioning
confidence: 99%
“…Researchers suggested that probiotics reduced the ROS activation evoked by radiation via the production of antioxidant enzymes such as superoxide dismutase, GSH peroxidase, GSH reductase, and catalase 22,23 . Shokri et al demonstrated that melatonin with its antioxidant property can decrease oxidative damage induced by radiofrequency electromagnetic radiation (RF-EMR) of mobile phones on testis tissue 24 . Moreover, melatonin has been reported to have an important anti-apoptotic action by attenuating the production of ROS and pro-apoptotic proteins, such as BAX 25 .…”
Section: Discussionmentioning
confidence: 99%